Laboratory Tests Assessment of a Mechanical Sensor-less MPPT Control Strategy for Tidal Turbines (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The purpose of this study is to demonstrate through towing tank experiments the effectiveness of a novel sensor-less Maximum Power Point Tracking (MPPT) control for Tidal Stream Turbines (TST) under fluctuations of the onset flow. Ocean energies will play a crucial role in the renewable energy sector over the next decades. Instream turbines for tidal currents are a rapidly maturing technology to exploit a highly predictable energy source. However, short-term fluctuations on the inflow velocity caused by waves or turbulence determine fatigue loads that affect system reliability. Power control strategies to maximize the energy yield can be also used to mitigate the effects of transient loading on drivetrain components.Aim of this paper is to present a straightforward and robust MPPT control method based on the linear relationship between the current and voltage squared of the generator's DC outputs. The method requires pre-determined turbine characteristics to establish the control reference that is effective across operating conditions. The proposed MPPT model was derived mathematically through linearization and simplifications of the turbine power conversion system and validated by model tests carried out in the wave-towing tank facility of CNR-INM in Rome, Italy, using the 1.5 m diameter Tidal Turbine Testing (TTT) device developed at the Queen’s University Belfast (QUB). In the study, a conventional TSR control method was also considered in order to perform a comparative analysis of system response to inflow speed fluctuations with time scales comparable to turbine revolution periods. TSR control was tested using two control references: TSR = 5 (design point) and TSR = 6 (over-speed zone) to verify the operation of the turbine under different loading conditions. The tests were conducted in two scenarios: calm water (steady state) and unsteady inflow with a regular (sinusoidal or monochromatic) waveform, with amplitude chosen to simulate an extreme wave case.The power output was measured from the turbine during regular wave conditions and compared to results from steady flow to assess the impact of wave-induced velocity on turbine performance (Fig. 1). Test results showed that by using the proposed MPPT control strategy, the algorithms converged to the maximum power coefficient (Fig. 2), which validates the proposed methodology. Results also demonstrated the capability of the proposed MPPT to significantly reduce mechanical loads fluctuations as compared to the TSR control.In the full-length paper, the proposed MPPT control strategy is outlined, the test methodology, set-up and conditions are described, and main results are presented and discussed.